2015
DOI: 10.1038/srep18224
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of OLR1 and PCSK9 Gene Polymorphisms on Ischemic Stroke: Evidence from a Meta-Analysis

Abstract: Both OLR1 and PCSK9 genes are associated with atherosclerosis, cardiovascular disease and ischemic stroke. The overall prevalence of PCSK9 rs505151 and OLR1 rs11053646 variants in ischemic stroke were 0.005 and 0.116, respectively. However, to date, association between these polymorphisms and ischemic stroke remains inconclusive. Therefore, this first meta-analysis was carried out to clarify the presumed influence of these polymorphisms on ischemic stroke. All eligible case-control and cohort studies that met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…In a recent meta-analysis of seven case-control studies, it was observed that OLR1 SNP rs11053646 dominant and co-dominant models were significantly associated with ischemic stroke (28). In the present study, OLR1 SNP rs11053646 recessive and co-dominant models were not significantly associated with the risk of FP artery disease.…”
Section: Discussioncontrasting
confidence: 55%
“…In a recent meta-analysis of seven case-control studies, it was observed that OLR1 SNP rs11053646 dominant and co-dominant models were significantly associated with ischemic stroke (28). In the present study, OLR1 SNP rs11053646 recessive and co-dominant models were not significantly associated with the risk of FP artery disease.…”
Section: Discussioncontrasting
confidence: 55%
“…Gain‐of‐function and loss‐of‐function PCSK9 mutations are associated with hypercholesterolemia and hypocholesterolemia, respectively . Moreover, PCSK9 polymorphisms have been reported to be associated with LDL‐C levels, LDL‐C lowering response to statins, and risk of premature CVD and ischemic stroke …”
Section: Discussionmentioning
confidence: 99%
“…10,21,23,32 Like studies on statin effects, several clinical trials and genetic studies have explored the effects of PCSK9 inhibitors on lipid levels, coronary heart disease, mortality, stroke, T2D and cognitive effects; these studies are often hampered by small sample sizes and offer conflicting evidence that can impact our understanding of new indications, safety considerations, and side effects. 12,3335 Hence, we developed a list of 11 hypothesis-driven phenotypes with careful definitions to evaluate the evidence of association of PCSK9 variants with phenotypes of interest in concurrent literature. 21,24,26,27…”
Section: Discussionmentioning
confidence: 99%
“…A handful of small studies have shown suggestive evidence for the association between PCSK9 variants and ischemic stroke. 12,35,38 However, larger studies have offered conflicting evidence. Two recent meta-analyses using genetic data 39 and randomized clinical data 40 showed no association between PCSK9 inhibition and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%